2019
DOI: 10.1193/102116eqs176m
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Scenario Spectra (CSS) for Hazard-Consistent Analysis of Engineering Systems

Abstract: Objective assessment of the seismic response of engineering systems is achievable through estimating the rate of exceedance (risk) of the engineering-demand parameters (EDPs), which are usually obtained by performing dynamic analyses with incrementally scaled seed ground motions. However, assigning rates of occurrence to such EDPs is difficult because the input ground motions are inconsistent with those that go into the hazard estimation. The Conditional Scenario Spectra (CSS) are a set of realistic ground-mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…The plan dimensions of each one are 117 ft (35.66 m) × 97 ft (29.56 m), and the total height is 49 ft (14.93 m), 97 ft (29.56 m), 193 ft (58.92 m), and 289 ft (88 m), respectively. These structures are an extension of the 8-story framing system studied by Arteta and Abrahamson (2019). The structural system comprises gravity load columns in the center of the structure with external special moment resisting frames (SMRF) to resist lateral seismic loading and the tributary gravity loading.…”
Section: Case Study: Response Of Ductile Rc Framesmentioning
confidence: 99%
See 2 more Smart Citations
“…The plan dimensions of each one are 117 ft (35.66 m) × 97 ft (29.56 m), and the total height is 49 ft (14.93 m), 97 ft (29.56 m), 193 ft (58.92 m), and 289 ft (88 m), respectively. These structures are an extension of the 8-story framing system studied by Arteta and Abrahamson (2019). The structural system comprises gravity load columns in the center of the structure with external special moment resisting frames (SMRF) to resist lateral seismic loading and the tributary gravity loading.…”
Section: Case Study: Response Of Ductile Rc Framesmentioning
confidence: 99%
“…Furthermore, the analysis must include the dynamic characteristics of the structures evaluated, for example, elastic periods and elongated period, which are correlated with the building height. These structures are an extension of the 8-story framing system studied by Arteta and Abrahamson (2019). The structural system comprises gravity load columns in the center of the structure with external special moment resisting frames (SMRF) to resist lateral seismic loading and the tributary gravity loading.…”
Section: Case-study Seismic Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficiency of Sa(T 1 ) with respect to the spectral shape effect can also be corrected by hazard-consistent record selection. [20][21][22] However, for the pulse-like ground motions, it has been shown that ɛ is insufficient with respect to the ratio of the pulse period to the fundamental period of the structure (T p / T 1 ), which is the key parameter affecting the response. 23 Vector-valued IMs that incorporate the spectral ordinates at periods other than T 1 have been proposed to overcome the insufficiency of the Sa(T 1 ) with respect to T p 24,25 ; however, the effectiveness of the period-dependent spectral quantities may change depending on the degree of nonlinearity of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Baker and Cornell discussed the significance of using Sa(T 1 ) and ε (the number of standard deviations between the spectral acceleration of a record and the mean of a ground‐motion model at the given period) as a vector IM, because the latter parameter is an indicator of spectral shape (ie, peaks or valleys in a response spectrum) and yields better predictions of structural response. The insufficiency of Sa(T 1 ) with respect to the spectral shape effect can also be corrected by hazard‐consistent record selection . However, for the pulse‐like ground motions, it has been shown that ɛ is insufficient with respect to the ratio of the pulse period to the fundamental period of the structure (T p /T 1 ), which is the key parameter affecting the response .…”
Section: Introductionmentioning
confidence: 99%